The biomechanics of the umbilical cord Wharton Jelly: Roles in hemodynamic proficiency and resistance to compression. (December 2019) - Brunelli, R.; De Spirito, M.; Giancotti, A.; Palmieri, V.; Parasassi, T.; Di Mascio, D.; Flammini, G.; D'Ambrosio, V.; Monti, M.; Boccaccio, A.; Pappalettere, C.; Ficarella, E.; et al.
Abstract: The umbilical cord is a complex structure containing three vessels, one straight vein and two coiled arteries, encased by the Wharton Jelly (WJ) a spongy structure made of collagen and hydrated macromolecules. Fetal blood reaches the placenta through the arteries and flows back to the fetus through the vein. The role of the WJ in maintaining cord circulation proficiency and the ultimate reason for arterial coiling still lack of reasonable mechanistic interpretations. We performed biaxial tension tests and evidenced significant differences in the mechanical properties of the core and peripheral WJ. The core region, located between the arteries and the vein, resulted rather stiffer close to the fetus. Finite element modelling and optimization based inverse method were used to create 2D and 3D models of the cord and to simulate stress distribution in different hemodynamic conditions, compressive loads and arterial coiling. We recorded a facilitated stress transmission from the arteries to the vein through the soft core of periplacental WJ. This condition generates a pressure gradient that boosts the venous backflow circulation towards the fetus. Peripheral WJ allows arteries to act as pressure buffering chambers during the cardiac diastole and helps to dissipate compressive forces away from vessels. Altered WJ biomechanics may represent the structural basis of cord vulnerability in many high-risk clinical conditions.